Bacillus velezensis HBXN2020 alleviates Salmonella Typhimurium infection in mice by improving intestinal barrier integrity and reducing inflammation - Linkang Wang; Haiyan Wang; Xinxin Li; Mengyuan Zhu; Dongyang Gao; Dayue Hu; Zhixuan Xiong; Xiangmin Li; Ping Qian (eLife)
Bacillus velezensis is a species of Bacillus that has been widely investigated because of its broad-spectrum antimicrobial activity. However, most studies on B. velezensis have focused on the biocontrol of plant diseases, with few reports on antagonizing Salmonella Typhimurium infections. In this investigation, it was discovered that B. velezensis HBXN2020, which was isolated from healthy black pigs, possessed strong anti-stress and broad-spectrum antibacterial activity. Importantly, B. velezensis HBXN2020 did not cause any adverse side effects in mice when administered at various doses (1×107, 1×108, and 1×109 CFU) for 14 days. Supplementing B. velezensis HBXN2020 spores, either as a curative or preventive measure, dramatically reduced the levels of S. Typhimurium ATCC14028 in the mice’s feces, ileum, cecum, and colon, as well as the disease activity index (DAI), in a model of infection caused by this pathogen in mice. Additionally, supplementing B. velezensis HBXN2020 spores significantly regulated cytokine levels (Tnfa, Il1b, Il6, and Il10) and maintained the expression of tight junction proteins and mucin protein. Most importantly, adding B. velezensis HBXN2020 spores to the colonic microbiota improved its stability and increased the amount of beneficial bacteria (Lactobacillus and Akkermansia). All together, B. velezensis HBXN2020 can improve intestinal microbiota stability and barrier integrity and reduce inflammation to help treat infection by S. Typhimurium.